Production and Life History of Paragnetina Media (Walker) (Insecta: Plecoptera) in a Central Wisconsin Stream - Radomski, Paul J. (University of Wisconsin-Stevens Point, College of Natural Resources, 1986)
The life history and production of the stonefly Paragnetina media (Walker) were studied in the lower Tomorrow River, a central Wisconsin stream, from June 1983 to August 1984. Adults exhibited a prolonged synchronous emergence beginning in early June. Individuals emerging early in the emergence period were on average statistically larger (p < 0.05) than those emerging later. Females deposited a mean of 4 egg masses in the laboratory, and mean fecundity was 1473 eggs. Eggs were kept at 5 constant temperatures (range 5-30 degrees C) in the laboratory. The percentage of eggs that hatched generally increased with increasing water temperature. Hatching time (days after oviposition at which 10%, 50%, and 90% of the eggs hatched) decreased with increasing water temperature, and the relationships between the two variables were well described by a hyperbola over the temperature range 15-25 degrees C; therefore, the time taken for development was expressed in units of degree-days (DD) above a threshold temperature. Hatching time for fertilized eggs was shorter than for unfertilized eggs. Larvae exhibited a complex semivoltine life cycle, with either a 2, 3, or mixed (2 and 3), year period of development. Length frequency analysis indicated variability in the life cycle duration depending on the time of egg hatch. Larvae that hatched in late summer following emergence required 3 years for development; whereas, larvae that hatched the following spring required about 2 years. The size-frequency distributions and the Janetschek method indicated ca. 26 instars for males and 30 instars for females. In later instars, female larvae were distinctly larger than males. Annual production, calculated from the sum of male and female production estimates using the size frequency method with a CPI of 940 d, was 7.13 g wet weight/m2 riffle, with P/B ratios of 5.04 (cohort) and 1.96 (annual). Production by females from 76% of total production.